Penentuan Faktor-Faktor yang Mempengaruhi Tingkat Fertilitas Di Indonesia Tahun 2017 Dengan Metode Multiple Classification Analysis (Analisis Data SDKI 2017) - Vivy Maharani; Annisa Putri Ramadhanty; Galang Madya Putra; Iqbal Mukti Pratama; Risni Julaeni Yuhan (Bina Nusantara University, 2020)
Fertility is the ability to produce offspring associated with female fertility. The desired condition is for the population to grow in balance as a prerequisite for achieving a population without growth, where fertility, mortality rates are declining, and distribution is more evenly distributed. To achieve a Balanced Growing Population Condition (PTS), a total fertility rate (TFR) of 2.1 per woman is expected in 2015. However, based on the results of the 2017 IDHS fertility rate in Indonesia is 2.4. This has not met the desired conditions to achieve the Balanced Growing Population (PTS) condition. For this problem, it is necessary to do further research to find out the factors that affect the level of fertility or the number of children born to women. In this study, researchers used the Multiple Classification Analysis (MCA) method to determine the factors that influence the number of births. The results and discussion show that a mother who knows her ovulation cycle and / or lives in a city has an average number of children who are smaller than a mother who does not know her ovulation cycle and / or resides in the village. This happens because a mother who knows her ovulation cycle is more able to control the incidence of pregnancy compared to a mother who does not know her ovulation cycle.